Randomized study evaluating testosterone recovery using short-versus long-acting luteinizing hormone releasing hormone agonists - Pai, Howard Huaihan; Pickles, Tom; Keyes, Mira; Jones, Stuart; McDonald, Rachel E.; Lesperance, Mary; Berthelet, Eric (Canadian Urological Association Journal, 2013)
Introduction: We sought to compare the rate of return of testosterone levels and sexual function in men with prostate cancer receiving longer acting, 3-month preparation of luteinizing hormone- releasing hormone agonist (L-LHRH-A) versus shorter acting, 1-month preparation of luteinizing hormone-releasing hormone agonist (S-LHRH-A). Methods and Materials: Men with low to intermediate risk localized prostate cancer were randomized to either L-LHRH-A (2-3 month duration LHRH-A) or S-LHRH-A (6-1 month duration LHRH-A) of androgen suppression therapy (AST) and prostate brachytherapy using iodine-125 radioisotopes. Serum total testosterone levels and PSA were recorded every 2 months for 2 years. Results: A planned target sample size of 100 was not achieved due to insufficient accrual. A total of 55 patients were randomized and 46 were used for analysis. The median time to recovery of testosterone to baseline levels (calculated from end of AST) was 8 and 4 months in the L-LHRH-A and S-LHRH-A arms, respectively (p = 0.268). The median time to testosterone recovery to lower limit of reference range was 4 and 2 months respectively (p = 0.087). Interpretation: This randomized study, which failed to reach accrual target, showed a trend towards more rapid recovery of testosterone levels using shorter acting LHRH-A. Another randomized study would be required to validate these findings. Currently, there is insufficient evidence to recommend the use of shorter acting LHRH-A as a means of providing more rapid recovery of testosterone levels. Introduction : Nous avons voulu comparer la vitesse de retour des taux de testostérone et de la fonction sexuelle chez des hommes atteints d’un cancer de la prostate recevant un agoniste de la LHRH à longue durée d’action pendant 3 mois ou un agoniste de la LHRH à courte durée d’action pendant 1 mois. Matériel et méthodologie : Des hommes atteints d’un cancer de la prostate localisé avec risque faible à intermédiaire ont été randomisés pour recevoir soit un agoniste de la LHRH à longue durée d’action (2 doses trimestrielles) soit un antagoniste de la LHRH à courte durée d’action (6 doses mensuelles) comme traitement antiandrogène et une brachythérapie prostatique avec des radioisotopes de l’iode 125. Les taux sériques de testostérone totale et d’APS ont été notés tous les 2 mois pendant 2 ans. Résultats : L’échantillon prévu au départ de 100 patients n’a pu être obtenu en raison d’un recrutement insuffisant. Au total, 55 patients ont été randomisés et 46 ont été inclus dans les analyses. L’intervalle médian de retour à des taux normaux de testostérone (calculés à partir de la fin du traitement antiandrogène) était de 8 et 4 mois dans les groupes sous agoniste de la LHRH à longue et à courte durée d’action, respectivement (p = 0,268). L’intervalle médian requis pour que les taux de testostérone atteignent la limite inférieure des valeurs de référence était de 4 et 2 mois, respectivement (p = 0,087). Interprétation : Cette étude randomisée, où on n’a pas réussi à obtenir le nombre de patients voulu, a montré une tendance vers un retour plus rapide des taux de testostérone avec un traitement par agoniste de la LHRH à courte durée d’action. Une autre étude randomisée serait nécessaire pour valider ces résultats. Actuellement, on ne dispose pas de suffisamment de données pour recommander un agoniste de la LHRH à courte durée d’action comme moyen pour ramener les taux de testostérone plus rapidement à la normale.